The influence of written items in the construction of grammar tests - Buedo, Jimena (2011)
Testing, as McNamara (2000) expresses, is a universal feature of social life and as such it attempts to examine how people perform in relation to others to make decisions about their social roles. This concept also applies to language testing, which involves gathering information and making judgement within a context of specific purposes and goals (Frendo, 2009). Testing is of critical importance in shaping the teaching process and the decisions about the students‟ performance. Therefore, this research aimed to find out to what extent the test results obtained by in-company intermediate students were influenced by the type of written item chosen by the teacher in the construction of grammar tests. The study also explored whether previous training in class affected the test takers‟ performance. The difference between closed-items and open tasks, between items presented in isolation and in context was also highlighted in the hope of raising awareness of the range of results that might be attained with different test formats. Findings showed that the type of test item chosen to evaluate in-company intermediate students‟ knowledge of grammar in the written medium appeared to have influenced their test results.